Spectral analysis by XANES reveals that GPNMB influences the chemical composition of intact melanosomes - Haraszti, Tamás; Trantow, Colleen M.; Hedberg-Buenz, Adam; Grunze, Michael; Anderson, Michael G. (Pigment cell & melanoma research, 2011)
GPNMB is a unique melanosomal protein. Unlike many melanosomal proteins, GPNMB has not been associated with any forms of albinism, and it is unclear whether GPNMB has any direct influence on melanosomes. Here, melanosomes from congenic strains of C57BL/6J mice mutant for Gpnmb are compared to strain-matched controls using standard transmission electron microscopy and synchrotron-based X-ray absorption near-edge structure analysis (XANES). Whereas electron microscopy did not detect any ultrastructural changes in melanosomes lacking functional GPNMB, XANES uncovered multiple spectral phenotypes. These results directly demonstrate that GPNMB influences the chemical composition of melanosomes and more broadly illustrate the potential for using genetic approaches in combination with nano-imaging technologies to study organelle biology.